Human rights in Malaysia - Zul Kepli, Mohd Yazid (2013)
Malaysia is a unique country. The concept of unity within diversity is often encouraged in country with multiracial community like Malaysia. For example, the ethnic groups in Malaysia can be divided into the Malays (50.4%), Chinese (23.7%), indigenous (11%), Indians (7.1%) and others (7.8%). As a multi-ethnic, multicultural and multilingual society, Malaysia has a relatively peaceful environment since its independence in 1957, with the exception of the 13 May 1969 incident which resulted in the death of between 196 to 2000 people. This paper argues that racial integration remains fragile in Malaysia after more than 50 years of independence. Malaysian society is still deeply divided with various human right issues; the majority Malays controlled the government, while the Chinese, the largest minority, dominated the economics of the nation. This paper analyses the concept of unity within diversity in a multi-ethnic, multicultural and multilingual community like Malaysia and argues that the current system suffered from serious flaws which prevented a proper integration between races. This is reflected by the unprecedented rise of racial and religious violent in 2010; churches and temples being burned and mosques being vandalized and defaced. This article also looks at the common problems uniquely faced by the different races in Malaysia and proceeds with a series of possible actions to be taken to ensure a safer and brighter future. This article also looks at the current lacuna in law which persistently fuelled unnecessary racial and religious tension. This article concludes that inadequate legal protections and mechanisms must be addressed, protection to all must be ensured (regardless of races and religion) and some affirmative action should be taken to ensure that the interest of all races is protected. The lessons will also be valuable for other countries with multiracial community.